Underdevelopment in Kenya : the political economy of neo-colonialism, 1964-1971 - Leys, Colin (Berkeley : University of California Press, 1975)
This book examines the historical transformation of Kenyan society from the beginnings of Kenya in the late 1800s to about 1970. Kenya is a regional centre for multi-national capitalism in Eastern Africa controlled by a corrupt and avaricious local ruling group, an increasingly oppressive country of wealth for the few and continuing poverty and deprivation for the masses. Kenya has continued to operate, since formal independence, as an ally of imperialism, a base for the British military presence in the Indian Ocean and, in the cases of both Somalia and latterly Tanzania, as a substantial external opposition to progressive regimes.
Includes bibliographical references and index.
lje 25/01/2018
Loans
Keywords: Economic history; Politics and government; Social conditions; Kenya